The Reaction of the City of London to the Quebec Resolutions, 1864-1866 - Smith, Andrew (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2006)
AbstractThis paper examines how British investors reacted when the Quebec Resolutions were published in the fall of 1864. Although the responses of bond markets are briefly considered, the paper is mainly based on non-quantitative sources such as newspaper editorials and correspondence. Examining why British investors generally approved of the constitutional plan contained in the Quebec Resolutions is useful because it illuminates such important themes as the place of imported capital in Canadian state formation, the role of Britain in Confederation, and the viability of interest-group explanations for the making of colonial policy. The ideas of British investors are also important because British capital helped to finance the public works that were a sine qua non of Confederation. In 1866, Joseph Howe identified pressure from the bondholders of unprofitable Canadian railways as one of the major factors driving the British government’s support of Confederation. Although Tom Naylor and other historians have made use of Howe’s insight, the role of the investors has been ignored by both Ged Martin and by those scholars who advance an ideological-origins explanation of Confederation. This paper will help remedy this oversight and is a step towards a viable materialist interpretation of why Confederation happened in the 1860s.